Effects of short-term and chronic olanzapine treatment on immediate early gene protein and tyrosine hydroxylase immunoreactivity in the rat locus coeruleus and medial prefrontal cortex - Verma, V. (2011)
10.1016/j.neuroscience.2006.08.010